Life-cycle portfolio choice with imperfect predictors - Michaelides, Alexander; Zhang, Yuxin (Journal of Banking & Finance, 2022)
We study quantitatively how uncertainty in expected stock return predictability affects life-cycle portfolio choice and wealth accumulation in the presence of undiversifiable labor income risk. Households filter information about future expected returns from observed predictors and realized stock returns. Therefore, optimal portfolio choice does not only depend on financial wealth and age, as in more traditional life-cycle models. Counterfactuals demonstrate the magnitude of portfolio demand changes that depend on perceptions about underlying expected returns. On average, life-cycle asset allocation becomes more conservative than models with either i.i.d. stock returns, or with clearer signals about expected stock returns.